Ecoenzymatic stoichiometry can reflect microbial resource limitation, substrate quality, or both in forest soils. (April 2022) - Zheng, Haifeng; Vesterdal, Lars; Schmidt, Inger Kappel; Rousk, Johannes
Abstract: Many studies have used the relative activities of extracellular enzymes associated with microbial carbon (C), nitrogen (N) and phosphorus (P) acquisition to infer the relative C vs. nutrient limitation of the microbial community. However, recent experimental and theoretical evidence has shown that the use of ecoenzymatic ratio to infer limiting microbial resources may be invalid. We added the two contrasting leaf litters ash ( Fraxinus excelsior L., relatively more labile and nutrient rich) and oak ( Quercus robur L.), into samples of mineral soils to validate the use of ecoenzymatic stoichiometry to reflect microbial resource limitation. The litter treatments were also combined with N and P addition treatments to push microbial communities toward stronger C limitation. The microbial resource limitations were examined in all treatments by the responses in microbial respiration, bacterial and fungal growth, microbial community composition, and by detecting the responses of microbial growth to factorial C and nutrient additions in short-term limiting factor assays (LFAs). High ratios of β-1, 4-glucosidase (BG) to β-1, 4-N-acetylglucosaminidase (NAG) + leucine aminopeptidase (LAP) (>2:1) contrasted with the expected reduction in C limitation after initial litter inputs. The high ratio was mainly driven by an increase in BG activity associated with high energy supply and high microbial rates of metabolism induced by added labile C substrates. During the later incubation period (7–56 days), decreasing respiration and bacterial and fungal growth rates reflected increased microbial C limitation in all treatments. An increasing BG/(NAG + LAP) ratio was in line with increasing microbial C limitation in the ash treatment where cellulose dominated as microbial C source, but a decreasing BG/(NAG + LAP) ratio was inconsistent with the temporal dynamics in microbial C limitation in the oak treatment where substrates other than cellulose (i.e., microbial necromass and lignin) dominated as C source late in the incubation. The increased BG/(NAG + LAP) ratio was in line with intensified microbial C limitation by NP addition, which was mainly due to the stimulated BG activity. In the oak and litter plus NP treatments, fungal growth was stimulated and NAG - an enzyme targeting amino sugars - was increased, presumably to meet the fungal C demand by utilizing microbial necromass - partly consisting of amino sugar polymers. Taken together, these results suggest that variation in substrate quality, availability and how these matched the present microbial energy allocation strategy and resource allocation to enzyme production caused a substantial variation in the BG/(NAG + LAP) ratio, thereby disconnecting the ratio from unambiguously reflecting the microbial resource limitation. Highlights: Ecoenzymatic stoichiometry hypothesis was tested by several experiments. The BG/(NAG + LAP) ratios contrasted with microbial C limitation after litter inputs. Increasing microbial C limitation induces higher BG/(NAG + LAP) ratios in labile litter. Increasing microbial C limitation induces lower BG/(NAG + LAP) ratios in recalcitrant litter. Ecoenzymatic ratios can capture microbial C limitation induced by NP addition.